2019
DOI: 10.1177/0950017019871244
|View full text |Cite
|
Sign up to set email alerts
|

The Same, Only Different: Doing Management in the Intersection between Work and Private Life for Men and Women in Small-scale Enterprises

Abstract: The aim of this article is to elucidate how male and female managers of small-scale enterprises in Norway and Sweden relate to and experience the intersection between work and private life. A qualitative content analysis was adopted to explore interviews with 18 managers. The analysis resulted in three primary categories: conflict as a part of the deal, using management to construct balance, and management identity contributing to enrichment. A key theme that emerged was doing management. Both men and women re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 51 publications
2
22
0
4
Order By: Relevance
“…A part-time contract often implies less income and more domestic work and care of children, which are factors that strengthen feminine capital (Huppatz, 2009 ). Thus, as in the study of the Scandinavian managers (Hagqvist et al, 2020 ), women seem to benefit from adhering to masculine capital. The two last factors concern the domestic domain, having a partner and children at home.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…A part-time contract often implies less income and more domestic work and care of children, which are factors that strengthen feminine capital (Huppatz, 2009 ). Thus, as in the study of the Scandinavian managers (Hagqvist et al, 2020 ), women seem to benefit from adhering to masculine capital. The two last factors concern the domestic domain, having a partner and children at home.…”
Section: Discussionmentioning
confidence: 69%
“…Women often find themselves balancing between being the main career and being equal (in terms of participation in the work life), which seems to have a negative effect on their well-being (Hagqvist, 2016 ). In a qualitative study of Scandinavian managers, the authors found that female interviewees strongly identified with the masculine norm as the good worker while they also emphasized the importance of support from family and friends to uphold this role as a good worker (Hagqvist et al, 2020 ). To find broader support for the phenomenon of the embodiment of enrichment, this study should be replicated in other countries and settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Common reasons for these conditions include a lack of financial resources, the manager’s limited interest in OSH issues, an absence of employee representation, insufficient OSH inspections and limited support from occupational health services and other human resource consultants 9 , 10 , 11 ) . Another obstacle for OSH investments in SSEs can be that the manager, who is often the owner, has great work demands, many work tasks, long and irregular working hours, and difficulties in balancing their work and private life 12 , 13 ) . The complex work situation of SSE managers can result in insufficient knowledge about OSH regulations and about how to implement structured OSH management systems 9 , 14 , 15 ) .…”
mentioning
confidence: 99%